KEBIJAKAN PERATURAN PERUNDANG-UNDANGAN TERHADAP SPESIALISASI HAKIM DALAM MENGADILI PERKARA - Ferry Asril (Ensiklopedia of Journal, 2022)
The specialization of the judge has no influence on the decision that was handed down because as long as no legal action is taken, then the decision is considered correct and there is no doubt about the decision. This paper conducts a study of the policy of the legislation on the specialization of judges in adjudicating cases and the reasons for the need for specialization of judges in adjudicating a case. Thus, it can be formulated precisely the specificity of the judge in adjudicating a case. This research is seen from the type is a normative legal research. Meanwhile, judging from its nature, this research is descriptive, namely research that provides a clear and detailed description of the problems studied. Legislative policies regarding the specialization of judges in adjudicating cases have been determined based on the absolute competence of a judicial body, namely regarding the authority of which judicial bodies to examine, hear, and decide on a case, namely general courts, religious courts, military courts, and administrative courts. state effort. Specialization of judges in adjudicating cases is very necessary because it aims to develop the expertise and expertise of judges in adjudicating cases. In addition, in order to increase productivity in examinations which will indirectly affect the disparity of decisions.